2005
DOI: 10.1111/j.1460-9568.2005.03973.x
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine depletion increases the power and coherence of β‐oscillations in the cerebral cortex and subthalamic nucleus of the awake rat

Abstract: Local field potentials (LFPs) recorded from the subthalamic nucleus (STN) of untreated patients implanted with stimulation electrodes for the treatment of Parkinson's disease (PD) demonstrate strong coherence with the cortical electroencephalogram over the beta-frequency range (15-30 Hz). However, studies in animal models of PD emphasize increased temporal coupling in cortico-basal ganglia circuits at substantially lower frequencies, undermining the potential usefulness of these models. Here we show that 6-hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

36
275
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 375 publications
(312 citation statements)
references
References 68 publications
36
275
0
1
Order By: Relevance
“…YKP10A also induced a specific increase in beta-2 activity not observed with the other drugs. Pronounced increases in beta oscillations have also been observed after dopamine depletion in the rat (Sharott et al, 2005). This increase in beta-2 activity combined with YKP10A's clinical profile that resembled that of the drugs known to affect dopamine transmission and preliminary in vitro results (see Introduction) thus lends further support to the notion that this compound affects dopamine signaling.…”
Section: Drug Effects On the Waking Eegsupporting
confidence: 60%
“…YKP10A also induced a specific increase in beta-2 activity not observed with the other drugs. Pronounced increases in beta oscillations have also been observed after dopamine depletion in the rat (Sharott et al, 2005). This increase in beta-2 activity combined with YKP10A's clinical profile that resembled that of the drugs known to affect dopamine transmission and preliminary in vitro results (see Introduction) thus lends further support to the notion that this compound affects dopamine signaling.…”
Section: Drug Effects On the Waking Eegsupporting
confidence: 60%
“…To further evaluate the changes at specific frequency bands, we calculated the normalized spectrum before, during, and after laser stimulation. We found that optogenetic stimulation of SChIs robustly increased oscillation power across higher frequency bands conventionally defined as alpha (8)(9)(10)(11)(12)(13)(14)(15), beta (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30), low gamma (30-60 Hz), and high gamma (60-100 Hz), but not lower frequency bands of delta (1-4 Hz) or theta (4-8 Hz) (Fig. 2 E and F; n = 7 mice).…”
Section: Resultsmentioning
confidence: 99%
“…A hallmark of PD pathology is chronic reduction of dopamine input to CBT circuits due to midbrain dopaminergic neuron loss. Loss of midbrain dopamine increases beta oscillation power and coherence in PD animal models (14,15). Similarly, acute reduction of dopamine locally in the striatum increases striatal beta oscillations (16).…”
mentioning
confidence: 99%
“…Dopaminergic medication and active movements are known to decrease STN beta synchronization (Brown et al 2001;Foffani et al 2005;Kuhn et al 2004;Levy et al 2002;Marsden et al 2001b;Priori et al 2002Priori et al , 2004 and deep brain stimulation in the STN may alleviate PD symptoms by disrupting this oscillatory activity (Brown et al 2004;Filali et al 2004;Jahanshahi et al 2000;Lozano et al 2002). It was previously hypothesized that dopamine action on the striatum acts as a filter for cortical input to the STN (Doyle et al 2005;Magill et al 2001Magill et al , 2004Sharott et al 2005). Thus the increase in number of STN cells with oscillatory beta activity might reflect the degree of nigrostriatal dopamine deficiency.…”
Section: Discussionmentioning
confidence: 99%